Trials for international crimes in Asia / edited by Kirsten Sellars. - Sellars, Kirsten (Cambridge University Press, 2016)
The issue of international crimes is highly topical in Asia, with still-resonant claims against the Japanese for war crimes, and deep schisms resulting from crimes in Bangladesh, Cambodia, and East Timor. Over the years, the region has hosted a succession of tribunals, from those held in Manila, Singapore and Tokyo after the Asia-Pacific War to those currently running in Dhaka and Phnom Penh. This book draws on extensive new research and offers the first comprehensive legal appraisal of the Asian trials. As well as the famous tribunals, it also considers lesser-known examples, such as the Dutch and Soviet trials of the Japanese, the Cambodian trial of the Khmer Rouge, and the Indonesian trials of their own military personnel. It focuses on their approach to the elements of international crimes, and their contribution to general theories of liability. In the process, this book challenges some orthodoxies about the development of international criminal law.